The free trade agreements of North America - Ivan Dujić (Međunarodni Problemi)
The definition of North America as a sub-region of the New World from the end of the Cold War to the post-Cold War era is still a perennial problem. The paper focuses on the analysis of the status of three countries in North America during the period from 1980 through 2022. By using the comparative method, content analysis from a legal point of view, and historiographical and statistical methods, the paper offers an answer to the research question: Can Canada, Mexico, and the United States nourish the idea of North America as a common area? Divided into two periods – before and after 2001, the paper points to the importance of the bilateral Canada-United States Free Trade Agreement (CUSFTA), which was superseded by the North American Free Trade Agreement (NAFTA) as a trilateral agreement involving Canada, Mexico, and the US. Further on, NAFTA was substituted by the Canada-United States-Mexico Agreement (CUSMA) as the final version. CUSMA was created in the years of the growing trends towards the weakening of democracy in Mexico and the US. The conclusion of this paper is grounded on the findings related to this sub-region of the New World.